Guided Endodontic Access in a Calcified Central Incisor: A Conservative Alternative for Endodontic Therapy - Freire, Bernardo Barbosa; Vianna, Stephane; Nascimento, Eduarda Helena Leandro; Freire, Marcus; Chilvarquer, Israel (Iranian Endodontic Journal, 2021)
Guided endodontic access is a promising method to treat teeth with pulp calcification. This report aimed to describe a case of root canal treatment performed through guided endodontic access in a calcified anterior tooth with apical periodontitis. A 23-year-old female with a history of trauma 10 years ago in the anterior maxilla was referred to the dental office. Her chief complaint was discolouration of the left central incisor crown. The tooth was sensitive to percussion and responded negatively to pulp sensitivity tests. The periapical radiography showed pulp calcification and periapical radiolucency. Cone-beam computed tomography (CBCT) was obtained to allow a more detailed view of the pulp canal and the periapical area. An intraoral scan was performed and the standard tessellation language (STL) archive was combined with digital imaging and communications on medicine (DICOM) images from CBCT in the Implant Viewer software. Subsequently, a 3D model was designed and printed to guide the endodontic access in position and appropriate angulation for dental instrumentation. The mold was positioned on the patient’s tooth and the root canal treatment was performed. After two years, complete healing of periapical tissues was observed. This method facilitates the drill targeting during access, reducing the risk of deviations and perforations.